(untitled) (Revista Brasileira Multidisciplinar, 2013)
Population aging is a Brazilian reality and a challenging aspect for public health since functional changes that are inherent to such process occur which should be taken into consideration in order to provide the elderly with good quality of life so that they can go through this process healthly. This review article aims to discuss the issue of aging from the perspective of nutrition and physical activity, highlighting the main nutrition and physical factors that affect the quality of human life during the aging process considering the raise in life expectancy and the increasing participation of the elderly in society, especially in developing countries like Brazil. The knowledge of these causes and the intervention of nutritionists and fitness trainers will allow such population to have its dietary needs met according to its needs, physical training tailored to the conditions of their bodies and, consequently, better health and independence to continue performing day-to-day activities.